Attention Deficit/Hyperactivity, Disorder, Legislation, School and PAE – Brief analysis (Research, Society and Development, 2021)
Attention Deficit Hyperactivity Disorder is a neurobehavioral disorder that has consequences for learning. However, it is not understood as a special educational need. Therefore, the present study is justified by the need to analyze the support given to students with ADHD, in the municipal education system in the city of Saquarema, State of Rio de Janeiro, clarifying about the disorder, punctuating the legislation that deals with the theme. , the support offered by the municipality to students with ADHD as well as its effectiveness related to the Basic Education Development Index (IDEB). For this purpose, descriptive research was used at the Edilson Vignoli Marins Municipal School, as well as a literary review in publications, journals, academic works and articles on the topic and its relevant aspects, using keywords such as education, IDEB, Program of Support for Educating (PAE), Saquarema, ADHD, selected from databases such as Pubmed, Scielo, Google Scholar, virtual libraries, among others, as a time cut of eleven years (2008 to 2019). The results obtained were exposed in subtitles, by which concepts and general characteristics of the disorder were exposed, as well as its history as such; the legislation that deals with the subject and/or lack thereof; the city of Saquarema, its educational public policy to face the issue (Program for Supporting Educating – PAE) and the effectiveness of this registered by IDEB and the descriptive research on the Municipal School Edilson Vignoli Martins, one of the centers of the PAE. Finally, the finals considerations about the study were presented.